Mycobacterium leprae and Mycobacterium lepromatosis in small mammals in Midwest Brazil - Beatriz Silva Nogueira; Maerle Oliveira Maia; Ravena Fernanda Braga de Mendonça; Luciano Nakazato; Valéria Dutra (Brazilian Journal of Infectious Diseases)
Leprosy is a chronic infectious disease caused by the bacilli Mycobacterium leprae and Mycobacterium lepromatosis. In addition to humans, animals such as nine-banded armadillos and red squirrels are species naturally infected. The objective of this study was to investigate the presence of M. leprae and M. lepromatosis in non-volant small mammals of the order Didelphimorphia and Rodentia through Polymerase Chain Reaction (PCR) assay. During 2015 and 2018, field expeditions were carried out in three municipalities, covering biotic elements of the Amazon and Cerrado biomes, in the Mato Grosso State, Midwest of Brazil. A specific primer for repetitive sequences of the genomic DNA of M. leprae and M. lepromatosis targeting the RLEP and RLPM gene, respectively, was used to screen for these agents. The molecular detection of M. leprae DNA in the samples was 13.8%. M. lepromatosis was not detected. The present study reports a description of M. leprae in small non-volant mammals in Brazil.